Diseño de una máquina automatizada para serigrafía textil en la empresa Ágil Línea deportiva ubicada en la ciudad de Bogotá D.C. (2021)
In this project we designed an automated textile screen printing machine for the company Ágil Línea Deportiva. This with the intention of improving the operation times, the quality of the final product and give the company the opportunity to be more competitive in its market. As a first step, the current situation of the textile screen printing machines present in the market is studied, studying their operating characteristics. The purpose of this is to propose the functional mode of the machine to be designed, focusing on the input and output variables and the systems needed to transform them. After this, the design alternatives of the machine are proposed in order to select the most adequate one. Once the best alternative is selected, the detailed design of each of the systems that compose it is carried out, sizing the parts in compliance with the failure criteria. After obtaining the drawings and the parts that make up the machine, the required manuals are prepared, such as the operation, safety, maintenance and installation manuals. Finally, an evaluation of the environmental impact of the machine and a financial study that shows the profitability of the machine for the company are carried out.